Civil-military cooperation: Integrated logistics in response to the COVID-19 crisis - Jo\~ao Reis (Logistics, 2021)
Background: This article addresses the civil-military cooperation in response to the COVID-19 crisis. In early 2021, the number of daily infections and the growing number of COVID-19 hospitalizations in Portugal were dramatic, reaching the highest rates in the world. In response, the Armed Forces were engaged and played a significant role in helping the National Health Service (NHS). The NHS is just one of many existing examples which demonstrate the relevance of logistical support from the Armed Forces so that civil institutions can return to a sustainable and autonomous situation. Methods: In order to understand and describe this real-life phenomenon, a qualitative and exploratory case study was conducted. Several sources of data collection were used for triangulation and corroboration. Results: The results suggest that, in emergency situations, logistical operations of the Armed Forces in support of civil society are divided into four major areas: planning and organizational activities; priority setting; combat service support; and training and self-reliance. Conclusions: Once the four areas of action of the Armed Forces were identified, the response to the COVID-19 crisis became more evident, as civil entities were able to make requests suited to military capabilities.
Keywords: 650; Armed Forces; civil society; COVID-19; emergency situations; logistic support; sustainability